Artificial Intelligences in English Teaching and Learning: A Systematic Research Review - Rahmanto, Andik; Indah, Rohmani Nur (English Education Study Program Faculty of Teacher Training and Education, 2023)
Technological developments cannot be separated from learning, including the use of Artificial Intelligence (AI), which has a tremendous impact on learning, both positive and negative. If used in the right way and in the right way, AI will have a significant effect on learning. This research aims to comprehensively review the use of AI in English language learning and teaching. This research method is a systematic research review that is part of qualitative research using the PICOC (Population-Intervention-Comparison-Outcomes-Context) technique. The aspect of the research discussion is how AI plays in English language learning. AI has a huge impact on the learning system and students' interest in learning English. The research results show that AI if used in the correct procedures, will really help teachers in teaching and further increase students' interest in learning English. Keywords: Artificial Intelligence (AI), Teaching learning development.